Rejecting Domestic Violence in Malaysia Based on The Qur’an and Prophetic Traditions - Mohammad Hidir Baharudin; Rahmawati Mohd Yusoff; Nadzrah Ahmad (Journal of Asian Wisdom and Islamic Behavior, 2023)
Gender equality in terms of economic participation and social standing of women appears to have contributed to violations of women’s rights. Compared to their peers with higher social positions, women with poor financial and social status are more likely to become victims of domestic violence abuse. As a result, women’s economic empowerment is critical to ensuring equal social treatment. Inequality in gender treatment can lead to abuse, harassment, and violence in the future. Perhaps women in Malaysia are economically under-empowered and have a social standing equivalent to men, they are more vulnerable to abuse. Should the people be concerned about women’s rights, which are already enshrined in the Qur’an and Prophetic Traditions, these breaches and violations are unacceptable. Hence, this research aims to examine the governing Qur’anic and Prophetic Traditions principles on women’s socio-economic rights and the preservation of their social rights in the face of domestic violence. The analysis is based on a qualitative and descriptive cross-sectional analysis of the governing statutes, reported cases, and data gathered from the respective administrative authorities. The research found that the low socioeconomic status of women is not a factor in domestic violence, as professional women also become a victim of domestic violence.